Lifestyle Analysis of Infertile Couples at a Rural Hospital - Review Over Twenty Years - Samal, Swarnlata L; Karpate, Shilpaja J; Kanchan, Dhadwe (Nepal Journal of Obstetrics and Gynaecology, 2011)
DOI: http://dx.doi.org/10.3126/njog.v5i1.5057 NJOG 2010 Jul-Aug; 5(1): 26-31